Alashiya, Caphtor/Keftiu, and Eastern Mediterranean Trade: Recent Studies in Cypriote Archaeology and History. A Review Article - Knapp, A. Bernard
on L. Hellbing, Alasia Problems; D. E. McCaslin, Stone Anchors in Antiquity: Coastal Settlements and Maritine Trade Routes in the Eastern Mediterranean: J. Strange, Caphtor/Keftiu.